Applications of multi-objective evolutionary algorithms in economics and finance: A survey - Castillo Tapia, Ma. Guadalupe; Coello Coello, Carlos A. (2007 IEEE Congress on Evolutionary Computation, 2007)
This paper provides a state-of-the-art survey of applications of multi-objective evolutionary algorithms in economics and finance reported in the specialized literature. A taxonomy of applications within this area is proposed, and a brief review of the most representative research reported to date is then provided. In the final part of the paper, some potential paths for future research within this area are identified.